“But not as detailed as including teaching the private part”: Malaysian preschool teachers’ understanding on the implementation of sexuality education in preschools - Wan Nawi, Wan Norfadillah; Kai Sze, Annie Wong; Yeong, Lim Yeong; Ling, Yip Chan; Ibrahim, Azirah; Jing, Voon Shi (Southeast Asia Early Childhood Journal, 2021)
This article aimed to discuss the implementation of sexuality education in the preschool context in Malaysia based on preschool teachers’ understanding. Past studies have reassured that teachers have played an important role in ensuring the success of early childhood sexuality education program. Numerous local and Asian studies have highlighted that due to the lack of training and limited assess on sexuality related resources, the implementation of this program in preschool level remained vague. To close the gap, interviews were conducted to discover Malaysia preschool teachers’ content knowledge and delivery on sexuality education in the early years. Ten qualified and experienced preschool teachers from Klang Valley were recruited as the study respondents. Content analysis was employed to extract emerging themes based on the interview scripts. Findings have revealed that the respondents showed a varied understanding about sexuality education in early childhood context, where their thoughts were found heavily confined by the social and cultural norms acquired through their previous experiences, current cognitive understandings and comfort level. The analysis has also expressed a potential risk of misinterpretation on children’s sexual behaviors among the preschool teachers, due to their insufficient knowledge on children’s sexual development. Further to that, the local early year sexuality education was found to be delivered informally within children’s routine in preschool, serving as reminder when necessary rather than pre-planned activities. This study is expected to provide implication to aid useful evidences in enhancing current sexuality education program in the preschool context, and devising comprehensive teachers training module for betterment.